2006
DOI: 10.1115/1.2206202
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Congenital Septal Defect Closure and Reactivity Testing in Patient-Specific Models of the Pediatric Pulmonary Vasculature: A 3D Numerical Study With Fluid-Structure Interaction

Abstract: Clinical imaging methods are highly effective in the diagnosis of vascular pathologies, but they do not currently provide enough detail to shed light on the cause or progression of such diseases, and would be hard pressed to foresee the outcome of surgical interventions. Greater detail of and prediction capabilities for vascular hemodynamics and arterial mechanics are obtained here through the coupling of clinical imaging methods with computational techniques. Three-dimensional, patient-specific geometric reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…"top-hat" profile); this is not unreasonable since typical Womersley numbers found in the MPA are much greater than 1.0, indicating flat profiles [6]. Computational fluid dynamics studies from our group have confirmed that velocity profiles within the main PA are indeed flat over the pulsatile cycle [7]. The pressure and calculated velocity time-histories were then separated into individual cardiac cycles (n > 20) based on ECG gating.…”
Section: Discussionmentioning
confidence: 91%
“…"top-hat" profile); this is not unreasonable since typical Womersley numbers found in the MPA are much greater than 1.0, indicating flat profiles [6]. Computational fluid dynamics studies from our group have confirmed that velocity profiles within the main PA are indeed flat over the pulsatile cycle [7]. The pressure and calculated velocity time-histories were then separated into individual cardiac cycles (n > 20) based on ECG gating.…”
Section: Discussionmentioning
confidence: 91%
“…Meshes consisting of entirely tetrahedral elements are already being employed in complex anatomical domains with great success. 19,20,25 And for simpler anatomies, hexahedral unstructured grids can be readily implemented 14 as the boundary-layer mesh uniformity can be controlled with reasonable manual mesh generation effort. The algorithms for creating unstructured grids are also more amenable to automation.…”
Section: Mesh Generationmentioning
confidence: 99%
“…Steinman et al have attempted similar planning techniques towards the detection and removal of atherosclerotic plaques using unsteady pulsatile CFD simulations with geometries and boundary conditions prescribed using patient-specific MRI [64][65][66][67]. Similar methods were applied to other cardiovascular systems such as the abdominal aortic aneurism [16,31,32,54,80] endovascular grafts [16,20], pediatrics [19,30], coronary arteries [51,52], and congenital heart diseases [39,40]. However, all of these studies primarily utilize surgical planning methods towards analysis of a limited number of anatomical geometries, and no one to date has used such methods towards systematic geometric optimization by combining MRI and CFD.…”
Section: Introductionmentioning
confidence: 97%